Sistem Informasi Akuntansi Koperasi Berbasis Web Pada KPN “Sehati” RSUD Kota Sungai Penuh - Ridwan, Muhammad; Devitra , Joni (Jurnal Manajemen Sistem Informasi, 2023)
The role of information technology in the business world is very important. Especially helping business people in managing their business well. One aspect that really needs the role of information technology is the financial aspect. Because in this aspect errors often occur if business actors still manage finances manually. This is what is being experienced by KPN "Sehati" RSUD Kota Sungai Penuh at this time. It is not surprising that errors often occur when processing data, considering that the data processed by KPN "Sehati" RSUD Kota Sungai Penuh is quite large. To help overcome these problems, a system design in the form of a prototype is needed which can later help work to be more transparent and accountable in compiling financial reports if the system design has been implemented properly into a complete system. The method used to design this system using the prototyping method. The purpose of this system design is as the initial foundation for business actors in planning the development of existing systems into a more computerized and well-integrated form. So the hope is that later with the implementation of this prototype system, it will help answer the problems experienced before.